SYNTHESIS AND BIOLOGICAL EVALUATION OF NOVEL (2-OXO-3-(ARYLIMINO) INDOLIN-1-YL)-N-ARYL PROPANAMIDES AS ANTI-HUMAN IMMUNODEFICIENCY AGENTS - Debnath, Biplab; Wang, Ping; Yang, Liu-meng; Zheng, Yong-tang; Ganguly, Swastika (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Acquired immunodeficiency syndrome (AIDS) was first identified in the Western world in 1981. Since then, AIDS has been increasingly wide spreading, its rapid worldwide dissemination brought about by modern mass tourism. Isatin (1 H-indole-2, 3-Dione), an endogenous compound identified in many organisms, shows a wide range of biological activities. In view of the above details, we wish to report the synthesis and evaluation of novel isatin analogs, as promising anti-human immunodeficiency (HIV) agents. Methods: A series of novel isatin analogs (3a-3p) were synthesized, and their chemical structures were confirmed by nuclear magnetic resonance:1H, 13C, ESI-MS spectral data, and CHNS. Results: The compounds were evaluated as inhibitors of HIV type-1 in MT-4 cell cultures. Of these sixteen compounds, only 5 compounds showed potent anti-HIV activity. Conclusion: Evaluation of compound properties in silico showed that they possess significant drug-like characteristics.